Effect of Food Distribution on Northern Bobwhite Resource Selection - Rachel R. Gardner; John Maerz; Theron M Terhune II; Ira B Parnell; James A. Martin (National Quail Symposium Proceedings, 2022)
Supplemental feeding is a common management tactic used to increase survival and reproduction of northern bobwhite (Colinus virginianus; hereafter, bobwhite). Different supplemental feeding methods alter the distribution of resources across a landscape in unique ways and may influence the space use and resource selection of target species differently. Predators may concentrate their movements near fed sites, and different distributions of supplemental feed may encourage bobwhite to concentrate their movements closer to feed than other areas, thereby altering the potential for predator-prey interactions near feed. We used radio-tracked locations and movements in areas with stationary feeders (“feeder fed”) and nonsupplementally fed (“unfed”; study 1, year 1) or nonstationary “broadcast fed” (study 2, year 2) areas to compare resource selection within a Bayesian framework. Second- and third-order resource selection functions indicated bobwhite were more likely to occur in proximity to feeders and feedlines when available, but bobwhite resource selection was more strongly affected by feeders. These results demonstrate that different distributions of food resources can affect prey resource selection, potentially altering the probability of overlap between nontarget predator and target prey species. Managers of bobwhite populations should broadcast feed instead of using feeders to avoid concentrations of bobwhites, which may lead to reduced survival.
Keywords: Colinus virginianus; feeders; habitat use; resource selection; supplemental feeding; survival